2021
DOI: 10.1371/journal.ppat.1009423
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interplay between the co-opted Fis1 mitochondrial fission protein and membrane contact site proteins in supporting tombusvirus replication

Abstract: Plus-stranded RNA viruses have limited coding capacity and have to co-opt numerous pro-viral host factors to support their replication. Many of the co-opted host factors support the biogenesis of the viral replication compartments and the formation of viral replicase complexes on subverted subcellular membrane surfaces. Tomato bushy stunt virus (TBSV) exploits peroxisomal membranes, whereas the closely-related carnation Italian ringspot virus (CIRV) hijacks the outer membranes of mitochondria. How these organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Interestingly, both GFP-ATG8a and GFP-ATG8i were usurped into TBSV and CIRV VROs, forming small number of punctate structures (Figs 1C and S1A–S1C ). We also found that the minus stranded replicon RNA, which is the replication intermediate and marks the site of virus replication [ 49 , 89 ] was co-localized with p33 replication protein and ATG8a in the replication compartment in N . benthamiana replicating the closely-related cucumber necrosis (CNV) helper virus, which supplied the RdRp ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both GFP-ATG8a and GFP-ATG8i were usurped into TBSV and CIRV VROs, forming small number of punctate structures (Figs 1C and S1A–S1C ). We also found that the minus stranded replicon RNA, which is the replication intermediate and marks the site of virus replication [ 49 , 89 ] was co-localized with p33 replication protein and ATG8a in the replication compartment in N . benthamiana replicating the closely-related cucumber necrosis (CNV) helper virus, which supplied the RdRp ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, both GFP-ATG8a and GFP-ATG8i were usurped into TBSV and CIRV VROs, forming small number of punctate structures (Figs 1C and S1A-S1C). We also found that the minus stranded replicon RNA, which is the replication intermediate and marks the site of virus replication [49,89] was co-localized with p33 replication protein and ATG8a in the replication compartment in N. benthamiana replicating the closelyrelated cucumber necrosis (CNV) helper virus, which supplied the RdRp (S2 Fig) . Therefore, we suggest that ATG8a is recruited to VROs that are active in viral RNA synthesis. Based on these experiments, we conclude that ATG8 autophagy-related proteins are efficiently recruited by tombusviruses to VROs in N. benthamiana.…”
Section: Recruitment Of Atg8 Into Tombusvirus Vros In Plantsmentioning
confidence: 85%
See 1 more Smart Citation
“…In fact, phospholipid biosynthesis in TBSV-infected yeast and plant cells is clearly enhanced (Sharma et al, 2010;Xu and Nagy, 2017). Thus, it is reasonable to speculate that de novo sterol biosynthesis in the ER acts in close coordination with internal redistribution of pre-existing sterol pools, such as PM sterols (Lin et al, 2021) or even the esterified sterols accumulated in the cytoplasmic lipid bodies (Bouvier-Navé et al, 2010;Lara et al, 2018) (Figure 2), in order to meet the enhanced demand of these compounds triggered by virus replication. To establish the origin of these sterols is certainly an interesting subject for further studies, but either case it is clear that efficient virus replication in infected cells requires an active intracellular trafficking of these compounds.…”
Section: Phytosterols Enrichment At Virus Replication Sitesmentioning
confidence: 99%
“…As such, MCS dysregulation is a hallmark of several neurodegenerative disorders, as well as genetic and metabolic diseases [14][15][16][17][18]. Similarly, viral infections can trigger reorganization of organelle contacts to modulate organelle structure and function, and to establish a successful replication cycle [19][20][21][22][23][24][25][26][27]. Viruses are obligate parasites, indicating that they must co-opt existing cellular pathways and modulate their homeostatic functions to instead support viral replication.…”
Section: Introductionmentioning
confidence: 99%